The Effects of Dynamic Loading on Hysteretic Behavior of Frictional Dampers - Hamid Rahmani Samani; Masoud Mirtaheri; Amir Peyman Zandi; Hamid Bahai (Shock and Vibration)
During an earthquake excitation, a frictional damper may experience many cycles of dynamic loading. The effects of wear and heat induced by the cyclic loading result in the possible decay of the slippage load which subsequently reduce the energy absorption of the damper. In this paper, the effect of dynamic loading on hysteretic behavior of a special kind of frictional damper, namely, cylindrical frictional damper (CFD), is investigated by experimental means as well as numerical models which also account for coupled thermal-structural interaction. The damper is deemed to be more susceptible to thermal deformations due to the shrink-fit mechanism by which the device is assembled. The numerical models are validated experimentally and may be utilized for simulation of dynamic cyclic loading on frictional dampers. The results demonstrate that the slippage load is reduced gradually when subjected to consecutive cycles. This drift is attributed to thermal deformation. The verified numerical models are used to improve the geometry of the CFD. With the geometrical improvements implemented, the subsequent numerical studies confirmed that almost no degradation of the slippage load occurred. Furthermore, a dimensionless parameter is introduced by the authors which shows the effect of wear on the response of CFDs.